Smart City in Practice: Learn from Taipei City - Muhammad Iqbal (Journal of Governance and Public Policy, 2021)
The main aspects of building a smart city according to Frost and Sullivan in 2014 are smart governance, smart technology, smart infrastructure, smart healthcare, smart mobility, smart building, smart energy and smart citizens. The smart city's purpose is to form a comfortable, safe city and strengthen its competitiveness. Based on these indicators, Taipei City can become one of the cities with the best Smart City implementation globally. This article uses a qualitative approach with literature review techniques in data collection. This study's findings indicate that the Smart Education, Smart Transportation, Smart Social Housing and Smart Healthcare policies are essential policies in supporting the successful implementation of smart cities in Taipei City. The four main pillars in implementing smart city in Taipei City have integrated Artificial intelligence and big data in smart city governance in Taipei City.